"Being Heard": Qualitative Research Conundrums With Individuals With Developmental Disabilities. (October 2015) - Wilkenfeld, Bonnie Fader
This article examines qualitative research dilemmas encountered with participants who have communication, physical and cognitive impairments. A review of the extant literature indicates the importance of identifying and resolving these research conundrums. The author will describe a qualitative study on identity formation in individuals with developmental disabilities (IWDD) as a medium to identify and explore the various dilemmas encountered while utilizing in depth interviews. Issues which arose during the research process include concerns about the potential of participants to be vulnerable to coercion, upholding privacy/confidentiality, role confusion and expressive language barriers in participating in narrative discourse; access to participants was an additional concern. Findings from this study indicated that IWDD benefit from participation in qualitative research. Three overarching themes were manifested: being heard, helping others, and enjoying the process. Suggestions for addressing the various dilemmas which might inhibit IWDD from participating in qualitative research are discussed and implications for social work practice and social justice initiatives are delineated.